Lakes in toponymic prose of Belarusians: plots, motifs and cultural landscape - Valodzina, Tatsiana V. (Journal of the Belarusian State University. Philology, 2025)
The author of the article examines the toponymic prose associated with lakes as culturally marked elements of sacred topography, in its correlation with the actual ritual practice and worldview of Belarusians. Toponymic lore and legends are shown as informative texts that reflect the relationship between traditional communities, wildlife, and the supernatural dimension of cultural landscapes. Special attention is paid to the church sinks underground motif. The etiological motif of the appearance of the lake after the beggar’s visit fits into many legends about the travelling God, the test of which initiates several social attitudes in a person, thus bringing the corpus of such texts closer to folk-biblical legends.